Ekstraksi Minyak Atsiri Berbahan Sereh Dapur Berbantu Microwave - Hidayat, Ika Nurfitri ; Nurhandayani, Rina (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
In Indonesia kitchen lemongrass grow a lot in the yard,but not many people use it as essential oil. Therefore, this study aims to produce essential oil extraction using a new method using Microwave-Assisted Hydrodistillation (MAHD). Previous reseach states that the results obtained from this method are better because some fractions that produce the aroma of essential oils can be extracted. By using this method the time required is shorter than using conventional methods.GC-MS (Gas-Chromatography-Mass Spectometry) analysis was used to obtain the resuls of the componens in essential oils. The quality of essential oil products produced is far more than other methods, so the selling price is much more expensive. So extraction using this method is indeed better and also effective so that in the production of essential oils can done in greater quantities.